Formation conditions of hydrocarbon systems in the Turkmen sector of the South Caspian basin - U. S. Serikova; M. A. Allanazarova (Известия высших учебных заведений: Геология и разведка, 2023)
Background. The formation and placement conditions of hydrocarbon systems and their accumulation in the Turkmen sector of the South Caspian basin are considered.Aim. To model the existing hydrocarbon systems in the Turkmen sector of the Caspian Sea based on available data.Materials and methods. Statistical generalization and systematization of available data was carried out. Research materials included fund and reference sources, fieldwork data, and publications by Sh.F. Mehdiyev, I.S. Guliyev, M.Z. Rachinsky, S.S. Djibouti, S.A. Aliyev, V.Y. Kerimov, V.V. Kolodiya, etc.Data modeling was performed in the PetroMod software.Results. The conducted numerical modeling established the formation conditions of the key elements of hydrocarbon systems, including oil and gas mother strata, reservoirs, and seals. Hydrocarbon prospects were identified. The main spatial and temporal patterns in the development of generation, migration, and accumulation processes of hydrocarbon fluids were determined, along with the formation conditions of traps. A map depicting potentially promising areas, objects, and plays was drawn. Hydrocarbon prospects were identified. Directions for oil and gas prospecting and exploration in the Turkmen sector of the Caspian Sea were substantiated.